Sindrom Down: Skrining, Diagnosis, dan Konsekuensi Kesehatan: Tinjauan Pustaka - Zevanya, Evita (PT Kalbe Farma Tbk., 2025)
Down syndrome is congenital or genetic abnormality with extra chromosome 21 causing various clinical manifestations and health problem. Down syndrome ranked first as the most common cause of birth defect in Indonesia. Chromosomal abnormality cause Down syndrome children have a higher risk and more common health problems. Down syndrome can burden family or caregiver physically, socially, financially, and emotionally. Proper screening and diagnosis criteria need to be done to establish the diagnosis.